BUILDING A TRAINING MODEL FOR MEMBERS OF THE MUSIC UNIT POLICE IN THE SUB DETASEMEN KORPS MUSIK DETASEMEN MARKAS KORPS BRIMOB POLRI - Dwi Yan Okvarianto; Bambang Giyanto (DIA: Jurnal Administrasi Publik, 2026)
This research focuses on how to build a music unit training model for Polri members at the Music Corps Sub-Detachment Detachment of the Police Mobile Brigade Corps Headquarters. The main problem raised was the absence of guidelines for a model for implementing music unit training at the Sub-Department of Korsik Denma, Brimob Polri Corps. The training that has been carried out has not been fully effective in equipping members with the skills needed when carrying out their duties, so this research aims to identify and analyze the implementation of Music Training for Police Members which has been carried out at the Sub-Department of Korsik Denma Brimob Corps and Determine the relevant Training Model. To achieve this goal, researchers used descriptive research methods with a qualitative approach. This research involves collecting data through in-depth interviews with informants consisting of coaches and music unit members as well as other supporting informants. The data obtained is then analyzed to find relevant patterns and context. A qualitative approach was chosen because it can provide an in-depth understanding of phenomena that occur in the field, as well as facilitate interpretation of the experiences and perspectives of informants. The research results show that there are several important aspects in music unit training that need to be considered, including the design of the training curriculum, the use of teaching methods and materials as well as leadership support regarding the sustainability of the training program and infrastructure.